Student Literacy through Picture Book Media: Nurturing a Culture in Elementary Schools - Syafitri, Yoesrina Novia Vini; Rahman, Rahman; Aprilia, Aprilia; Pertiwi, Novalda (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2021)
The culture of student literacy is the main support in the progress of education in a country. The ability of literacy is believed by developed societies to be a very essential need for every human being. The better the person's literacy level will affect his or her ability to absorb knowledge in the learning process. Literacy skills are a basic ability that every student needs to have. Gerakan Literasi Sekolah exists as a government effort to develop a student literacy culture. This movement seeks students to read non-text books for 15 minutes before learning. As an effort to maximize the school literacy movement, picture book media are present as an alternative solution. According to their age range, the students show interest in the learning resources that attract attention. For encouraging students' interest in learning, especially in reading, picture book media can be used in maximizing literacy culture in elementary schools. This study may contribute to enrich research references in the language education field, especially about student literacy.